Lebih dari Sekedar Katalog Manuskrip: Jejak Intelektualisme Islam di Mindanao - Fadlan, Muhammad Nida' (Studia Islamika, 2019)
Oman Fathurahman, Kawashima Midori, and Labi Sarip Riwarung (eds.). 2019. The Library of an Islamic Scholar of Mindanao: The Collection of Sheik Muhammad Said bin Imam sa Bayang at the Al-Imam As-Saddiq (A.S.) Library, Marawi City, Philippines: An Annotated Catalogue with Essay. Tokyo: Institute of Asian, African, and Middle Eastern Studies, Sophia UniversityContemporary socio-political issues have dominated studies on Islam in the Southern Philippines. The lack of primary sources has caused discussions about the history of Islamic culture in the region to be relatively rare. This manuscript catalog could be the key. It reveals the existence of 4,215 pages of manuscripts and 3,224 pages of printed books (kitāb) of the Al-Imam As-Sadiq Library in Marawi City. It proposes a new method for compiling a manuscript catalog so that readers who are not too familiar with Islamic studies and philology may also enjoy reading. Besides offering a description of manuscripts, it also presents a mapping of intellectual works written by ulamas in Mindanao and their connection with the Muslim-Malay communities in other regions. Hence, this book will support further studies on intellectual networks in the Muslim community in Southeast Asia in general and Mindanao in particular.